Penerapan Platform DigiLearnHub Untuk Meningkatkan Kemampuan Literasi dan Numerasi Siswa Serta Pelayanan Administrasi di SMAS Kesuma Bakti - Priandika, Adhie Thyo; Saputra, Very Hendra; An’ars, M. Ghufroni; Darwis, Dedi (Universitas Teknokrat Indonesia, 2024)
SMAS Kesuma Bakti Bekri (SMAS-KBB) has several priority issues that need to be addressed, includingThe educational report score for literacy skills at SMAS-KBB is still categorized as poor, with a score of 33.33. The educational report score for numeracy skills at SMAS-KBB is also categorized as poor, with a score of 35.56. The management of the school's administrative and financial services system has not been optimized. Based on these priority issues, the proposed solutions areImplementing the DigiLearnHub Platform. Providing training and assistance to teachers in creating and designing engaging literacy and numeracy learning content to be used on the DigiLearnHub platform. Providing training and assistance to students on the use of the DigiLearnHub platform and the importance of improving literacy and numeracy learning as a foundation for mastering science and technology. Implementing an application that can be accessed digitally through the website and mobile for real-time School Administration System. Based on the evaluation results, there was an 84.85% improvement in teachers' ability to create literacy and numeracy learning content. Furthermore, based on post-test results conducted with students, there was an increase in the average student score, with literacy achieving 87.2 and numeracy 86.2. This indicates an improvement in literacy and numeracy learning quality, which is expected to prepare students for the ANBK. In addition, the school administrative service application has improved the school's administrative and financial services. According to survey results, 87% of students and parents expressed high satisfaction with the services provided through the school administration and financial application.